Geotechnical Site Investigation for IBS House Construction in Bukit Rambai, Melaka. A Case Study Using Mackintosh Probe Tests - Mohamad Azwan Ikhwat; Shahrun Nazida Salleh; Faisal Ananda (Civil Engineering Dept, Balikpapan State Polytechnics, 2025)
This research explores the challenges of assessing soil bearing capacity and strength for constructing an Industrialized Building System (IBS) house in Bukit Rambai, Melaka. It utilizes a cost-effective and portable method known as the Mackintosh Probe Test, which is particularly suitable for small-scale, low-risk projects. The need for this study is clear, as traditional methods like the Standard Penetration Test (SPT) can be too expensive for smaller residential developments, making the Mackintosh Probe a practical alternative for initial geotechnical assessments. The research hypothesizes that the Mackintosh Probe can provide reliable soil data for foundation design, helping to reduce costs while maintaining accuracy. The main goal of the study is to evaluate soil characteristics and bearing capacity using the Mackintosh Probe, supply essential data for safe foundation design, and establish a relationship between Mackintosh Probe results and SPT values, along with acceptable soil pressures. The methodology involved conducting six Mackintosh Probe tests on-site, recording blow counts for every 0.3 m of penetration, and analyzing soil consistency and bearing capacity through established correlations with SPT N-values. The findings revealed various soil layers, with the upper layers suitable for strip footings and deeper layers requiring pile foundations due to hard strata. The implications of this research are significant, as it demonstrates the Mackintosh Probe’s cost-effectiveness for IBS projects, potentially cutting investigation costs by up to 40%, while also highlighting the need for additional tests and localized correlation charts for tropical soils, like those in Malaysia. This study provides valuable insights for foundation design in similar contexts and encourages further research to improve the use of the Mackintosh Probe in tropical areas.